Fe and Cr phase separation in super and hyper duplex stainless steel plates and welds after very short aging times - Vahid A Hosseini; Mattias Thuvander; Kristina Lindgren; James Oliver; Nicklas Folkeson; Daniel Gonzalez; Leif Karlsson (Materials & Design, 2021)
Fe and Cr phase separation in ferrite, causing 475 °C-embrittlement, was studied after very short aging times in super duplex stainless steel (SDSS) and hyper duplex stainless steel (HDSS) plates and welds. Atom probe tomography showed that hot-rolled SDSS, experiencing significant metal working, had faster kinetics of phase separations compared to the SDSS and HDSS welds after 5 min aging at 475 °C. The surface of the 33-mm SDSS plate had faster Fe and Cr phase separation and larger toughness drop. A higher density of dislocations next to the austenite phase boundary in ferrite, detected by electron channeling contrast, can promote the phase separation at the surface of the plate with lower austenite spacing. The toughness dropped in HDSS welds after aging, but SDSS welds maintained their toughness. An inverse simulation method considering an initial sinusoidal nanometric Cr and Fe fluctuation showed that Ni increases the interdiffusion of Cr in the system, resulting a higher degree of phase separation in SDSS welds than the HDSS weld. Within the composition range of the studied SDSS and HDSS materials, the processing influences the Fe and Cr phase separation more than the variation in composition during short aging or typical fabrication times.